Field study of the fate of labelled fertilizer nitrate applied to barley and maize in sandy soils - Yusop, Mohd Khanif; Cleemput, O. Van; Baert, L. (1984)
The recovery in crop and soil of labelled fertilizer nitrate applied to barley and maize growing on a sandy soil was measured. The experimental plots, each measuring 4m × 4m, were situated on fields growing with barley and with maize. The barley received 50 kg N/ha as KNO3 enriched with 5.99 At.%15N excess while the maize received 113 kg N/ha as KNO3 labelled with 5.014 At.%15N excess. Otherwise, the plots were treated the same as the rest of the field. At harvesting, the barley and the maize plots were subdivided into nine and six sub-plots respectively. Plant samples, including the roots and soil samples up to 1 m depth were collected in each sub-plot. Fertilizer N recovery in the samples was measured. In the plants, the N derived from the fertilizer (Ndff) was 24.0% and 16.7% in barley and maize, respectively. The percentage of the applied fertilizer recovered by barley was 57%; for maize, only 18%. The movement of fertilizer N was restricted to the top 50 cm in the barley plot, whereas in the maize plot, the fertilizer N could be detected down to 90 cm. The amount of fertilizer N remaining in the soil at harvest was 32% for the barley and 68% for the maize plot. The loss of fertilizer N under barley was 10% and 14% under maize. The loss was attributed mainly to denitrification. The means and the variances of total N uptake by plants inside the15N plot and outside the15N plot were compared. They did not differ significantly, indicating that the results obtained from the15N plot can be extrapolated to the rest of the field.